Community-Based Art Therapy Program to Honor 9/11. Issue 2 (3rd April 2021) - Shipley, Melody J.; Coggins, Kim; Shipley, Kenneth C.; Ellison, David
ABSTRACT: With the increase of mental health problems among veterans and active duty service members since the terrorist attacks on 9/11, the need to provide effective mental health treatments has grown. This study focused on the experiences of thirty-seven active service members, veterans, and their families participating in community-based arts activities. Four themes were uncovered suggesting the experience was positive and expressing thoughts and feelings through art-making was therapeutic. Results indicated that art expression provided a way to reflect on the effects on the country, families, and individuals affected by 9/11. Understanding how participants experienced the event provides better understanding of how expressive arts events addressing grief and combat-related loss can be a beneficial component of community engagement and integration.